Establishing the connection between successful disposal of public assets and sustainable public procurement practice - Adoko Obicci, Peter; Mugurusi, Godfrey; Oluka Nagitta, Pross (Sustainable Futures, 2021)
The disposal of assets after their end-of-use is often considered the end-stage in the procurement cycle. Assets disposal in a public organization is its capacity to attach reusable value to its assets at their end of life. It is an area where the failure of the public procurement process is most attributed yet has the most potential for sustainable procurement practice. This paper examines the factors for the successful disposal of public assets and the public purchasers’ perceptions of how these factors contribute to a better understanding of sustainable procurement practice. Using a cross-sectional survey among key actors in the public procurement process, three key success factors, namely strategic assets management, strategic planning for assets disposal, and assets disposal mechanismsare identified; their effect on successful asset disposal is examined. The results indicate that the three broad factors studied are all important aspects for effective assets disposal. Yet, their effect on the success of the disposal of public assets process is somewhat varied. Based on the three factors’ statistical significance, we conclude that strategic assets’ planning is perhaps the most dominant factor for a successful assets disposal process and provides the most promise for sustainable procurement in public organizations. This study shows that strategic assets management, strategic planning for assets disposal, and the choice of assets disposal mechanisms are all critical enablers of successful disposal of public assets in public organizations and a precursor for sustainable procurement practice. But at the microlevel, disposal planning is by far the most significant enabler for successful assets’ disposal, and therefore a direct driver for sustainable procurement practice.
Keywords: Disposal; Public assets disposal; Sustainable public procurement; Asset life cycle